Heterogeneously Ni–Pd nanoparticle-catalyzed base-free formal C–S bond metathesis of thiols. Issue 31 (26th March 2021) - Mitamura, Kanju; Yatabe, Takafumi; Yamamoto, Kidai; Yabe, Tomohiro; Suzuki, Kosuke; Yamaguchi, Kazuya
Abstract : An efficient base-free synthesis of thioethers from various thiols has been achieved using Ni–Pd alloy nanoparticle catalysts supported on hydroxyapatite under an H2 atmosphere. Abstract : This study rationally designed a heterogeneously catalyzed system ( i.e., using Ni–Pd alloy nanoparticles supported on hydroxyapatite (Ni–Pd/HAP) under an H2 atmosphere) achieving an efficient base-free formal C–S bond metathesis of various thiols via suppression of the Ni catalysis deactivation.